(untitled) (Journal of Economics and Sustainability, 2023)
This paper aims to determine the technology readiness level of paddy farmers in MADA, KADA, and IADA BLS, Malaysia. Primary data were obtained through a face-to-face survey with paddy farmers in MADA, KADA, and IADA BLS using a structured questionnaire. A total of 315 respondents of MADA, 295 respondents of KADA, and 178 respondents of IADA BLS actively involved in paddy cultivation were interviewed. The technology readiness level of paddy farmers from three main granary areas is evaluated objectively and subjectively. The technology readiness index of paddy farmers is calculated to analyse the readiness level of paddy farmers. Thirty indicators are used to measure four dimensions of technology readiness, i.e., optimism, innovativeness, discomfort, and insecurity. The present study shows that 72.4%, 74.58%, and 74.16% of paddy farmers in MADA, KADA, and IADA BLS have a moderate readiness level to adopt the new technology in paddy cultivation. The four dimensions of the technology readiness index was evaluated to provide a better picture of the technology readiness level. All three granary areas have a score mean index (0.51-1.0) for technology readiness driver, optimism, and innovativeness, which indicate that the paddy farmers have a moderate and high level of optimism and innovativeness to adopt the new technology. However, the score means index for the negative factors of technology readiness for all three granary areas is in the quantile range (0.51-0.75), which means the paddy farmers have a moderate level of discomfort and insecurity. Thus, the result suggests that although the paddy farmers exhibit innovativeness and optimism, they also experience some discomfort and insecurity.